Gateway to Prosperity: The China-Pakistan Economic Corridor (CPEC) - Mehdi Shah (Review Journal of Social Psychology & Social Works, 2025)
A major part of China’s Belt and Road Initiative (BRI) is the China-Pakistan Economic Corridor (CPEC). It is a huge project that aims to improve economic integration and connectivity in the area. CPEC has had a big impact on Pakistan’s economy and on the politics of the area. It has led to the development of infrastructure, cooperation in energy, industrial growth, and cooperation in social and political issues. The narrative review method used in this study brings together information from academic books, government reports, and policy briefs to give a full picture of CPEC’s effects and problems. Key results show big improvements in trade connectivity, long-term energy use, and industrial diversification. However, there are still important issues like financial sustainability, security risks, and environmental degradation. To make sure fair and long-lasting growth, policy suggestions focus on managing debt, protecting the environment, including stakeholders, and open government. CPEC is a great example of how strategic international partnerships can help make an area more stable and prosperous. It could be used as a model for future global economic projects.